FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN BENIGNA PROSTAT HIPERPLASIA: A LITERATURE REVIEW - Nida Auliya Rosyad, (2020)
Benign prostatic hyperplasia is a common chronic condition that is observed in elderly men. Benign prostatic hyperplasia has become a major health problem for elderly men because of its associated symptoms and complications. Although this disease is not a life-threatening condition, benign prostatic hyperplasia has a bad effect that can interfere with the quality of life. This study aims to examine existing research to determine the best evidence related to the factors that influence the incidence of benign prostatic hyperplasia. Qualitative research using the study research method literature review by searching the literature using electronic databases namely PubMed and Science Direct and using a search engine that is Google Scholar by taking into account the inclusion criteria namely accessible journals full-text that discuss risk factors for the occurrence of benign prostatic hyperplasia with a time limit Past 10 years. Based on the literature review in 7 journals, there are 6 variables found. 5 variable factors are modifiable risk factors that can influence the incidence of benign prostatic hyperplasia. 1 other factor variable is irreversible. The risk factors that influence the incidence of benign prostatic hyperplasia are aging / age, obesity, smoking, alcohol consumption, physical activity/sports, and waist circumference.